Value relevance of stock option compensation disclosures of NASDAQ100 companies. - Choo, Boo Geok. (2008)
The objective of this research paper is to establish the relationship between the employee stock options expense that is disclosed as a footnote (permitted under Statement of Financial Accounting Standards (SFAS) No. 123) but not charged as an expense in the financial statement (Accounting Principles Board Opinion (APB) No. 25) and the market value of equity.